Alien plants invade more phylogenetically clustered community types and cause even stronger clustering. Issue 7 (6th May 2015) - Lososová, Zdeňka; de Bello, Francesco; Chytrý, Milan; Kühn, Ingolf; Pyšek, Petr; Sádlo, Jiří; Winter, Marten; Zelený, David
Abstract Aim Several hypotheses postulate that species invasion is affected by an interplay between the phylogenetic position of the invading species and the phylogenetic structure of the invaded community type. Some of them suggest that phylogenetic relatedness of invaders to native species promotes naturalization, because phylogenetically related alien species tend to have similar environmental adaptations as native species. Others predict that phylogenetic relatedness hampers naturalization because of stronger competition of aliens with native species and shared enemies. Here we ask how phylogenetic diversity of native species affects invasion across community types. Location Czech Republic. Methods All major plant community types at a national scale (n = 88) were characterized by their species pools, i.e. lists of species that can potentially occur there. Of the total number of 2306 species, 1785 were native, 246 were archaeophytes and 275 were neophytes. For each species pool, we related the number of alien species to the phylogenetic diversity of the native species pool, calculated as mean phylogenetic distance (MPD) and mean nearest taxon distance (MNTD), including null models. Results The number of alien species was related both to the phylogenetic structure of community types and to the phylogenetic position of alien species. Frequently disturbed herbaceous community types with strong phylogenetic clustering were more invaded than others, possibly due to disturbance acting as an environmental filter. Here, alien species increased the degree of phylogenetic clustering as they tended to be from the same lineages as native species. Such trends were not detected for phylogenetically more diverse community types such as forests. Main conclusions Our findings support the hypothesis that relatedness of invaders to native species promotes invasion because of their shared adaptations to the same environments. Alien species more strongly invade community types that are phylogenetically clustered, and because they tend to be related to native species, invaded community types become even more clustered.